Virtual Laboratory - Information In Education A Specific Factor Of The Communication System In The Form - Z.R. Mamadaliyeva (Genius Publishing Group, 2022)
The graduation qualification work is devoted to the introduction, organization and solution of virtual laboratory work in the educational process through special pedagogical software using information and communication technologies and the problems arising in this process and ways of their solution.
Keywords: Laboratory; virtual laboratory; sanitary laboratory; Chemistry